1976
DOI: 10.1071/pp9760173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sulphur Supply on the Seed Globulin Composition of Lupinus angustifolius

Abstract: Seeds from L. angustifolius grown at three levels of applied sulphur contain similar amounts of protein whereas the ratio of total nitrogen to total sulphur in the whole seed and in the extracted protein is greatly increased under sulphur deficiency. This large change in nitrogen to sulphur ratio is accompanied by suppression of the synthesis of conglutins α and γ which usually contain most of the sulphur-containing amino acids found in these seeds. This is balanced by synthesis of an increased amount of congl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
0
1

Year Published

1977
1977
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 0 publications
7
30
0
1
Order By: Relevance
“…Legumin was virtually undetectable under severe S deficiency. Similar changes were found in the more S-rich com-47 ponent of the storage proteins of lupin under S deficiency conditions (1).…”
supporting
confidence: 67%
“…Legumin was virtually undetectable under severe S deficiency. Similar changes were found in the more S-rich com-47 ponent of the storage proteins of lupin under S deficiency conditions (1).…”
supporting
confidence: 67%
“…In conditions of sulfur limitation, lupin seeds accumulate increased amounts of sulfur-poor storage proteins, and decreased amounts of relatively sulfur-rich proteins like conglutins-␣ and -␥ (Blagrove et al, 1976). Similarly, we have observed that mRNA coding for the very Cys-rich conglutin-␦ is diminished in control lupin seeds grown with low and medium sulfur compared with those grown in high sulfur medium (data not shown).…”
Section: Effects Of Manipulating Sulfur Supplysupporting
confidence: 52%
“…There are many reports of sulfur limitation evoking specific changes in protein profiles of seeds (Chandler et al, 1984;Gayler and Sykes, 1985), including narrow leaf lupin (Blagrove et al, 1976). In general, the accumulation of sulfur-rich proteins is down-regulated, whereas sulfur-poor proteins become overrepresented.…”
Section: Limits To the Accumulation Of Sulfur Amino Acids In Tg Lupinmentioning
confidence: 99%
See 2 more Smart Citations